2020
DOI: 10.1038/s41598-020-61105-z
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure, thermodynamic stability and high-temperature sensing properties of Er-α-SiAlON ceramics

Abstract: α-SiAlon ceramics have been in use as engineering ceramics in the most arduous industrial environments such as molten metal handling, cutting tools, gas turbine engines, extrusion molds, thermocouple sheaths, protective cover for high-temperature sensors, etc., owing to their outstanding mechanical, thermal and chemical stability. taking advantage of the intrinsic properties of α-SiAlons, we investigate, in this paper, the possibility of using the er-doped α-SiAlon (er-α-SiAlon) ceramic as a high-temperature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…x Si 12-m-n Al m+n O n N 16-n , where Li, Mg, Ca, Y, and/or a rare earth element refer to M, and by considering its ionic radius [138] or with using quenching. For entry of cations with considerable size in structure, the presence of other cations is required.…”
Section: α-Sialons Can Be Presented By the Chemical Formula M V+mentioning
confidence: 99%
See 1 more Smart Citation
“…x Si 12-m-n Al m+n O n N 16-n , where Li, Mg, Ca, Y, and/or a rare earth element refer to M, and by considering its ionic radius [138] or with using quenching. For entry of cations with considerable size in structure, the presence of other cations is required.…”
Section: α-Sialons Can Be Presented By the Chemical Formula M V+mentioning
confidence: 99%
“…α-SiAlONs are isostructural with α-Si 3 N 4 in which chemical binding of m and n (Si-N) are substituted by Al-N (m) and Al-O (n) bonds, respectively, the schematic diagram of which is shown in Figure2[136][137][138]. In addition, supplementary cation for the stability of crystal lattice of α-SiAlONs is needed.…”
mentioning
confidence: 99%
“…The N1s peak consists of three sub-peaks as shown in Figure 5 e. The weak sub-peak at the lowest binding energy corresponds to the N-Al, while the intense central peak corresponds to the N-Si bonds in the α-SiAlON lattice because the N1s binding energy for AlN is less than that for Si 3 N 4 [ 35 ]. In the α-SiAlON crystal, the Ln 3+ dopant (Ho 3+ ) occupies the seven-fold coordination site [ 5 , 21 ] for the charge compensation which arises due to the partial Al (Si)-O (N) substitution in the formation of the SiAlON lattice [ 3 ]. Hence, it is suggested that the broad sub-peak with the highest binding energy in Figure 5 e corresponds to the N-Ho bond.…”
Section: Resultsmentioning
confidence: 99%
“…On contrary, many other host materials, such as LaMgAl 11 O 19 [ 40 ], Y 2 O 3 [ 41 ], NaYF 4 [ 13 ], K 2 SiF 6 [ 12 ], etc., show a decrease in emission intensity due to concentration quenching at a high level of doping of the activators. An additional advantage of Ho-SiAlON ceramics as phosphors is that SiAlON ceramics have a very high laser damage threshold and high-temperature spectral stability [ 21 , 42 ] that make them suitable for high-power green emitting remote phosphors in extreme conditions [ 8 , 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation